Antibacterial Property Evaluation of Ethanolic Extract of Plantago major L. and Its Fractions - Prismawan, Deka; Michael; Gunawan, Gwyneth Yovela; Kambira, Pretty Falena Atmanda (Universitas Muhammadiyah Purwokerto, 2026)
The escalating global health crisis of antibiotic resistance necessitates the search for novel antibacterial agents from natural sources. This study investigated the potential of Plantago major L., a plant used in traditional medicine, as a source of antibacterial compounds. It aimed to evaluate the antibacterial activity of its ethanol extract and its polarity-based fractions against Escherichia coli and Staphylococcus aureus. Dried P. major L. leaves were extracted with ethanol using maceration. The crude extract was then fractionated using a sequential liquid-liquid extraction with hexane, ethyl acetate, and n-butanol. The antibacterial activity of the extract and all fractions was tested against S. aureus (ATCC 25923) and E. coli (ATCC 25922) using the broth microdilution method to determine the Minimum Inhibitory Concentration (MIC). Results revealed distinct antibacterial profiles based on fraction polarity. The ethyl acetate fraction exhibited the strongest activity against S. aureus with an MIC of 0.104 mg/mL, indicating the presence of potent semi-polar compounds like flavonoids effective against gram-positive bacteria. Conversely, the n-butanol fraction was most effective against E. coli with an MIC of 3.3 mg/mL, suggesting the role of hydrophilic compounds such as saponins in disrupting the more complex gram-negative membrane. The crude ethanol extract showed lower activity, confirming the critical role of fractionation in concentrating the bioactive compounds. Plantago major L. possesses significant antibacterial potential, with its active compounds concentrated in specific polarity-based fractions. These findings validate its traditional use and support its further development as an alternative therapy in the face of growing antibiotic resistance.